THE USE OF VIRTUAL LABORATORY TO IMPROVE STUDENTS' CONCEPTUAL UNDERSTANDING IN ACID BASE TITRATION SUBJECT - Erni; Copriady, Jimmi; Linda, Roza (International Journal of Educational Best Practices, 2019)
The research has been conducted to figure out the use of virtual laboratories on students' conceptual understanding of acid-base titration subject at SMAN 1 Tambusai. The study was an experimental research with one group pretest-posttest design. The sample consisted of one class, XI IPA2, a class that was treated with a virtual laboratory. The data analysis technique used was the t-test. Based on the results of the final data processing using the t-test, it was obtained that sig 5 ≤0.05; where 0,000 ≤ 0.05; so it was concluded that there were significant differences between the mean scores of the pretest and posttest. This shows that there is an increase by the use of virtual laboratories towards the students' conceptual understanding.